Morphological and functional changes of lungs with the complex effect of immobilization and hypothermia - K. M. Khamchiyev; Shandaulov, A. Kh.; S. S. Ibrayeva; A.A. Ostanin; A.K. Zhiyengaliyeva (International Journal of Psychosocial Rehabilitation, 2020)
In experiments on rats with the use of tetrapolar rheograph method and coloring of lungs tissue with hematoxylin and eosin were studied morphofunctional changes of pulmonary circulation during the combined influence of immobilization and hypothermia. It was determined that abnormalities run at the level of microvasculature vessels of lungs tissue and are accompanied by blood filling reduction, development of arteriolospasm signs, capillaries and post-capillary venules plethora with sustainable increase of vascular wall permeability.